Laparoscopic Supracervical Hysterectomy with In-Bag Morcellation in Very Large Uterus - Harald Krentel; Rudy Leon De Wilde (Case Reports in Medicine)
Laparoscopic supracervical hysterectomy (LASH) is a safe and fast minimally invasive approach in hysterectomy. In order to extract the uterine body from the abdominal cavity, one condition for LASH is the morcellation of the tissue. The intra-abdominal dissemination of benign and occult malignant uterine cells is a possible risk of this method, which can be avoided by the use of special bags for laparoscopic in-bag morcellation. We present a case of laparoscopic supracervical hysterectomy with in-bag morcellation in a uterus of more than 1400 g. and describe that this minimal-access surgery is safe and feasible even in very large uteri. This case report is registered in Research Registry under the UIN researchregistry1810.